The effect of institutional ownership on firm innovation: Evidence from Chinese listed firms - Zhao Rong; Xiaokai Wu; Philipp Boeing (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
Monitoring by institutional investors can act as an important mechanism to promote firm innovation. By investigating Chinese listed firms' patenting between 2002 and 2011, we find that the presence of institutional investors enhances firm innovation. Consistent with the monitoring view, we further find that (1) the effect of institutional investors on firm patenting mainly comes from mutual funds; (2) the effect is more pronounced when market competition is more intense; (3) the effect exists among private- and minor state-owned enterprises, but not among major state-owned enterprises. The above findings are robust when innovation quality is examined.
urn:nbn:de:bsz:180-madoc-419765
Keywords: G20; G32; O31; O32; O33; 330; Institutional investor; Firm innovation; Patenting; Mutual funds; China